2020
DOI: 10.1016/j.neuroimage.2020.117136
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of brain oxygen extraction and metabolism with [15O]-gas PET: A technical review in the era of PET/MRI

Abstract: Oxygen extraction fraction (OEF) and the cerebral metabolic rate of oxygen (CMRO 2 ) are key cerebral physiological parameters to identify at-risk cerebrovascular patients and understand brain health and function. PET imaging with [ 15 O]-oxygen tracers, either through continuous or bolus inhalation, provides non-invasive assessment of OEF and CMRO 2 . Numerous tracer delivery, PET acquisition, and kinetic modeling approaches have been adopte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 126 publications
(201 reference statements)
1
44
1
Order By: Relevance
“…There are other metabolic imaging approaches, such as 15 O PET and 17 O MRI ( Fan et al, 2020 , Zhu and Chen, 2017 ), which can potentially capture Warburg effect of gliomas. For example, 17 O MRI has detected decreased oxygen consumption in gliomas, presumably related to Warburg effect ( Paech et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are other metabolic imaging approaches, such as 15 O PET and 17 O MRI ( Fan et al, 2020 , Zhu and Chen, 2017 ), which can potentially capture Warburg effect of gliomas. For example, 17 O MRI has detected decreased oxygen consumption in gliomas, presumably related to Warburg effect ( Paech et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For healthy subjects, CBF 29 and CMRO 2 30, 31 are considerably lower in WM as compared to GM. Several studies have reported non-significant differences in the oxygen extraction fraction (OEF) between WM and GM in healthy subjects (see meta-analysis presented in Fan et al 2020 32 ) indicating a regional equilibrium between CBF and CMRO 2 . It follows that changes in venous hemoglobin saturation, along with venous CBV, will drive the WM BOLD signal contrast under hypercapnia.…”
Section: Discussionmentioning
confidence: 99%
“…Several MR contrast agents, such as paramagnetic nitroxide radicals (e.g., mito-TEMPO, 3-carbamoyl-PROXYL) and paramagnetic chemical exchange saturation transfer agents, have also been developed to evaluate the redox status in vivo [176][177][178]. As new MR techniques for imaging oxygen metabolism advance, the OEF and oxygen metabolism, as well as oxidative stress, will also be elucidated by MR imaging [179]. However, PET has the advantage of higher detection sensitivity at the nanomolar level [14], which suggests that the optimal approach will be multimodal imaging combining PET and MR [165,180].…”
Section: Development Of Imaging Techniques For Oxidative Stressmentioning
confidence: 99%